Civil discourse as a source of social consensus: significance in wartime - Fialko, Natalia (Filosofiya osvity. Philosophy of Education, 2023)
Peculiarities of civil discourse as a source and method of establishing social consensus are considered. The purpose of this article is to show the potential of civil discourse as a basis for obtaining a stable public consensus. The differences of civil discourse as oriented to a pragmatic result, in contrast to philosophical discourse as oriented to the search for truth for its own sake and rhetorical discourse as oriented to victory in a debate over an opponent at any cost within the rules of rhetoric, are clarified. The mutual conditionality of the development of the democratic culture of society and the unceasing deployment of open and free public discourse is emphasized. It was found that public discourse arises as an attempt to establish understanding between representatives of local discourses within individual social communities. Thus, social consensus emerges as a overlapping consensus between individual social communities of a certain society. Such public consensus appears as the next, higher level of legitimation that can be gained in open discourse. The importance of illegitimate coercion has been rethought: violence that destroys morality cannot be accepted under any circumstances, but attempts to temporarily limit the effect of morality in emergency situations (in particular, in conditions of war) can become the subject of civil discourse in order to reach a public consensus on the necessity and moral justification of armed resistance to aggression. Civil discourse is even more in demand in the space of global civil society, in particular, to achieve international consensus on the need to ensure the military defeat of the aggressor country. Another direction of the application of civil discourse is the determination of tasks and ways of post-war reconstruction of the victim country and post-war punishment and atonement for the crimes committed by the aggressor state.